2005
DOI: 10.14411/eje.2005.010
|View full text |Cite
|
Sign up to set email alerts
|

Abundance of non-target pests in transgenic Bt-maize: A farm scale study

Abstract: Abstract. The impact of transgenic Bt-maize, expressing the Cry1Ab protein, on aphids, leafhoppers, cutworms and wireworms was evaluated at the farm scale by comparing their abundance on Bt-plots and those sown with the isogenic variety over three consecutive growing seasons. The impact of Bt-maize was different on each of the three-herbivore groups. There were significantly more aphids on the Bt-maize but in terms of aphid species, the difference was only statistically significant for Sitobion avenae and not … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
45
0
2

Year Published

2008
2008
2020
2020

Publication Types

Select...
6
2
1

Relationship

1
8

Authors

Journals

citations
Cited by 70 publications
(50 citation statements)
references
References 28 publications
3
45
0
2
Order By: Relevance
“…Similarly to spiders and harvestmen (Řezáč et al 2006), we could not detect any treatment effect on the assemblage of carabid beetles in any of the study fields. Our results are thus congruent with previous findings (Volkmar & Freier 2003;Candolfi et al 2004;Pons et al 2005;Eizaguirre et al 2006;Farinos et al 2008;Balog et al 2011), including those from the Czech Republic. No significant negative effect of Bt maize on carabid beetles, rove beetles, and spiders was found in the study from south-easten part of the Czech Republic (Habuštová et al 2006) nor significant differences between Bt maize and izogenic cultivar were found in the occurrence of aphids, thrips, and predatory bugs (Sehnal et al 2004).…”
Section: Discussionsupporting
confidence: 93%
See 1 more Smart Citation
“…Similarly to spiders and harvestmen (Řezáč et al 2006), we could not detect any treatment effect on the assemblage of carabid beetles in any of the study fields. Our results are thus congruent with previous findings (Volkmar & Freier 2003;Candolfi et al 2004;Pons et al 2005;Eizaguirre et al 2006;Farinos et al 2008;Balog et al 2011), including those from the Czech Republic. No significant negative effect of Bt maize on carabid beetles, rove beetles, and spiders was found in the study from south-easten part of the Czech Republic (Habuštová et al 2006) nor significant differences between Bt maize and izogenic cultivar were found in the occurrence of aphids, thrips, and predatory bugs (Sehnal et al 2004).…”
Section: Discussionsupporting
confidence: 93%
“…In most cases, assemblages of epigeal arthropods seemed not to be affected by presence of transgenic Bt maize (Volkmar & Freier 2003;Candolfi et al 2004;Sehnal et al 2004;Habuštová et al 2005Habuštová et al , 2006Pons et al 2005;Eizaguirre et al 2006;Farinos et al 2008;Balog et al 2011; but see Wold et al 2001), and these results were repeated also for Bt cotton and vegetables (Leslie et al 2007;Torres & Ruberson 2007). Indeed, some authors conclude that compared to conventional farming, the use of transgenic plants enhances arthropod biodiversity in crop fields via reduced input of insecticides to the system (Ferry et al 2006;Leslie et al 2007).…”
mentioning
confidence: 96%
“…The vast majority of studies indicate no effect of such varieties on aphids. In most cases laboratory investigations concluded that aphids could not be affected because the toxin is not transported in the phloem sap on which these insects feed (Raps et al, 2001;Pons et al, 2005). However, there are also a few reports relating different GM plants, mentioned in introduction, pointing to the prospective, indirect action on these herbivores and their natural enemies (Lumbierres et al, 2004;Burgio et al, 2011;Stephens et al, 2012).…”
Section: Discussionmentioning
confidence: 99%
“…Even though aphid performance fell within the normal variation observed among conventional maize varieties, different studies reported that aphids perform better on Bt-maize than on near isogenic counterparts (e.g., Bourguet et al, 2002;Dutton et al, 2002;Lumbierres et al, 2004;Pons et al, 2005;Eizaguirre et al, 2006). With the larger colony densities of aphids on Bt-maize, more honeydew was produced, in turn increasing parasitoid longevity and rate of parasitism.…”
Section: Gmo Panel Assessmentmentioning
confidence: 92%